New findings on retinal microvascular changes in patients with primary COVID-19 infection: a longitudinal study - Zhang, Chenxi; Cheng, Shiyu; Chen, Huan; Yang, Jingyuan; Chen, Youxin (Frontiers in Immunology, 2024)
Purpose To investigate the longitudinal alterations of retinal microvasculature in patients with primary coronavirus disease 2019 (COVID-19) infection. Methods A cohort of participants, who had never been infected with COVID-19, was recruited between December 2022 and May 2023 at Peking Union Medical College Hospital in Beijing, China. Participants underwent comprehensive ophthalmologic examinations and fundus imaging, which included color fundus photography, autofluorescence photography, swept-source optical coherence tomography (SS-OCT) and SS-OCT angiography (SS-OCTA). If participants were infected with COVID-19 during the study, follow-ups with consistent imaging modality were conducted within one week and two months after recovery from the infection. Results 31 patients (61 eyes), with a mean age of 31.0 ± 7.2 years old, were eligible for this study. All participants contracted mild COVID-19 infection within one month of baseline data collection. The average period was 10.9 ± 2.0 days post-infection for the first follow-up and 61.0 ± 3.5 days for the second follow-up. No clinical retinal microvasculopathy features were observed during the follow-ups. However, SS-OCTA analysis showed a significant increase in macular vessel density (MVD) from 60.76 ± 2.88% at baseline to 61.59 ± 3.72%(p=0.015) at the first follow-up, which subsequently returned to the baseline level of 60.23 ± 3.33% (p=0.162) at the two-month follow-up. The foveal avascular zone (FAZ) remained stable during the follow-ups with areas of 0.339 ± 0.097mm2, 0.342 ± 0.093mm2, and 0.344 ± 0.098mm2 at the baseline, first follow-up (p=0.09) and second follow-up (p=0.052), respectively. Central macular thickness, cube volume and ganglion cell-inner plexiform layer showed a transient decrease at the first follow-up(p<0.001, p=0.039, p=0.002, respectively), and increased to baseline level at the two-month follow-up(p=0.401, p=0.368, p=0.438, respectively). Conclusion Mild COVID-19 infection may temporarily and reversibly impact retinal microvasculature, characterized by a transient increase in retinal blood flow during the early recovery phase, which returns to the pre-infection level two months post-infection.